Strategically oriented correction of mixed astigmatism in children - E. P. Tarutta (Российский офтальмологический журнал)
Purpose: evaluation of the remote functional and refractive results of mixed astigmatism correction in preschool children with “plus” cylinders in the framework of a long-time longitudinal study.Material and methods. 38 children (75 eyes) aged 1.5–7 years (averagely 4.2 years) with mixed astigmatism of 0.75 to 4.25 D (averagely 1.85 D) were followed up for 6-15 (averagely 7.3) years. At the first examination, all children were prescribed to permanently wear (+) cylinders of 0.5 D to 3.5 D. Over the follow-up period, (+) Cyl could be weakened in 24 eyes (32 %) due to a decrease in astigmatism, while (-) Sph had to be added in 24 eyes (32 %). due to an increased refraction. In cases when the full correction using a “plus” cylinder left an excessively large myopic defocus, the power of the “plus” cylinder was reduced so as not to add a “minus” sphere, and a second pair of glasses was prescribed for near vision, which offered a full correction of astigmatism with the “plus” cylinder.Results. After 6–15 years, astigmatism changed in 85 % of the examined eyes: it increased in 7 eyes (averagely, by 0.3 D) and decreased in 53 (averagely, by 0.9 D, p < 0.05; with the maximum reduction of 2.75 D). The spheric-equivalent refraction changed in 51 % of eyes, with an average increase of 0.53 D. The maximum increase of refraction was 2.8 D, while the maximum drop was 1.4 D. Visual acuity of the children who wore the prescribed eyeglasses permanently, showed after two years an increase, average achieving the level of 0.84, which by the end of the follow-up period achieved 0.99.Conclusion. The proposed plan of mixed astigmatism correction, which preserves residual weak myopic defocus, fully ensured both tactical and strategic effects: prevention and elimination of amblyopia, and containment of refraction myopization.